Zinc co-ordination by the DHHC cysteine-rich domain of the palmitoyltransferase Swf1 - González Montoro, María Ayelén (2013)
S-acylation, commonly known as palmitoylation, is a widespread post-translational modification of proteins that consists of the thioesterification of one or more cysteine residues with fatty acids. This modification is catalysed by a family of PATs (palmitoyltransferases), characterized by the presence of a 50-residue long DHHC-CRD (Asp-His-His-Cys cysteinerich domain). To gain knowledge on the structure–function relationships of these proteins, we carried out a randommutagenesis assay designed to uncover essential amino acids in Swf1, the yeast PAT responsible for the palmitoylation of SNARE (soluble N-ethylmaleimide-sensitive fusion protein-attachment protein receptor) proteins. We identified 21 novel loss-of-function mutations, which are mostly localized within the DHHC-CRD. Modelling of the tertiary structure of the Swf1 DHHC domain suggests that it could fold as a zinc-finger domain, co-ordinating two zinc atoms in a CCHC arrangement. All residues predicted to be involved in the co-ordination of zinc were found to be essential for Swf1 function in the screen. Moreover, these mutations result in unstable proteins, in agreement with a structural role for these zinc fingers. The conservation of amino acids predicted to form each zinc-binding pocket suggests a shared function, as the selective pressure to maintain them is lost upon mutation of one of them. A Swf1 orthologue that lacks one of the zinc-binding pockets is able to complement a yeast swf1Δ strain, possibly because a similar fold can be stabilized by hydrogen bonds instead of zinc co-ordination. Finally, we show directly that recombinant Swf1 DHHC-CRD is able to bind zinc. Sequence analyses of DHHC domains allowed us to present models of the zinc-binding properties for all PATs.